Effect of auditory training and speech reading on speech discrimination ability of children with hearing loss in Ibadan, Oyo State, Nigeria (2020)
Children with hearing loss have poor speech discrimination ability as a result of the loss of auditory capacity to recognize and discriminate speech, sounds. Past studies were focused largely on the rehabilitation of the auditory systems towards efficient speech recognition ability with little attention paid to the rehabilitation of speech discrimination difficulty. This study, therefore, was designed to determine the effect of auditory training and speech reading on the speech discrimination ability of children with hearing loss. The moderating effects of the degree and age of onset of hearing loss were also examined. The study adopted the pretest-posttest control group quasi-experimental design of 3x2x3 factorial matrix. Multi-stage sampling technique was used to select the three schools used, while the thirty participants involved were purposively selected based on their degree and onset of the hearing loss. The participants were randomly assigned into auditory training (10), speech reading (10) and control (10) groups. The treatment lasted ten weeks. The instruments used were the adapted version of the Clement Ayodele Bakare Speech Discrimination Test List (r = 0.75) and Masy Part LaForest Experimental Speech Sound Discrimination Test List (0.72). Data were analysed using Analysis of Covariance and Scheffe Post-hoc test at 0.05 level of significance. There was a significant main effect of treatment on the participants speech discrimination ability (F (2,13) = 10.008, partial2 = 0.56). Participants in the speech reading group had the highest mean score (49.00), followed by those in auditory training (42.33), while those in control group had the lowest mean (33.33). There was no two-way interaction effects of degree and onset of hearing loss on the speech discrimination ability of children with hearing loss. The study also revealed insignificant three-way interaction effects of treatment, degree, and onset of hearing loss on the speech discrimination ability. Auditory training and speech reading exercises were effective in enhancing speech discrimination ability of children with hearing loss in Ibadan, regardless of the degree and onset of hearing loss. However, speech reading showed better outcome than auditory training. Therefore, audiologists, hearing therapists and speech therapists should adopt these strategies towards improving the speech discrimination ability of children with hearing loss.